Joint reconstruction of non-overlapping magnetic particle imaging focus-field data. (24th March 2015) - Knopp, T; Them, K; Kaul, M; Gdaniec, N
Abstract: The focus field is a key component to enable clinical applications in magnetic particle imaging (MPI). Due to physiological constraints, the method of choice is to place the focus of a small acquisition volume at various static positions in space and acquire the full field-of-view using a multi-station approach. In the first experiments, overlapping drive-field patches were used and boundary artifacts between drive-field patches were reduced using image processing. In this work we show that artifact-free reconstruction of non-overlapping focus-field data is feasible by using a joint reconstruction algorithm. This enables maximum scanning efficiency in multi-station focus-field experiments, which is key for reaching sufficiently short acquisition times to image the human heart.